Kontribusi Kajian Muslimah terhadap Pencegahan Konflik Rumah Tangga: Studi Kasus di Ciampea - Muhammad Anshari Salam; Fachri Fachrudin; Muhammad Hidayat (AHKAM, 2026)
Although family resilience and the prevention of household conflict have received attention in studies of Islamic family law and the social sciences, research that specifically discusses the contribution of community-based Muslimah study forums in building household communication as a preventive mechanism for conflict remains limited. This study aims to analyze the contribution of the Forum Kajian Muslimah Ciampea in building household communication based on Islamic values as an effort to prevent household conflict from the perspective of Islamic law. This study used a qualitative approach with a case study design, involving nine participants consisting of the forum chairperson, administrators, active members, and study participants selected through purposive sampling. Data were collected through semi-structured interviews, participatory observation, and documentation, and were then analyzed using thematic analysis through the stages of data reduction, data display, verification, and conclusion drawing. The results show that the Forum Kajian Muslimah Ciampea serves as a space for internalizing Islamic values that shape household communication through the strengthening of a culture of deliberation, communication openness, emotional control, and social support among participants. This role contributes to preventing household conflict before it develops into more serious disputes. These findings contribute to the development of the concepts of ishlah, maqāṣid al-sharī‘ah, and family resilience theory in the context of community-based family development, as well as broaden understanding of the role of Muslimah communities as preventive agents in Muslim family life. The conclusion of the study emphasizes that household communication based on Islamic values plays an important role in strengthening family resilience. The implications of this study include theoretical contributions to the development of empirical Islamic family law literature and family communication, as well as practical implications for religious communities and policymakers in developing preventive and participatory strategies for preventing household conflict.